Perbedaan Tingkat Upah Pekerja di Sektor Manufaktur dan Jasa - Rafly Parenta Bano; Ridhwan Ridhwan (Universitas Musamus, Merauke, Papua, 2020)
This study aims to determine how wages differ among workers and to investigate the factors thatdetermine these wage differences in the manufacturing and service sectors in Indonesia. Multipleregression models with dummy variables are used to determine how the characteristics and quality ofworkers influence the difference in wages in the labor market in Indonesia. Worker factors such aseducation, work experience, gender and marital status explain around 24.8 percent of the variation inworkers' wages. The results of this study indicate the importance of the characteristics and quality ofworkers in determining the difference in the level of wages of workers, both in the manufacturing sectorand in the service sector. The independent variables in the model, namely higher education, workexperience, gender and marital status have a significant positive effect on the difference in wages ofworkers in the manufacturing and service sectors. Thus, this study highlights the importance of humanresources in increasing the income level of workers and reveals the fact that the quality of humanresources is not only important for reducing wage differentials but also helps in increasing the wage rateof workers.